2008
DOI: 10.1016/j.physbeh.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Fos expression at the cerebellum following non-contact arousal and mating behavior in male rats

Abstract: The cerebellum is considered a center underlying fine movements, cognition, memory and sexual responses. The latter feature led us to correlate sexual arousal and copulation in male rats with neural activity at the cerebellar cortex. Two behavioral paradigms were used in this investigation: the stimulation of males by distant receptive females (non-contact sexual stimulation), and the execution of up to three consecutive ejaculations. The vermis area of the cerebellum was removed following behavioral experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
3
15
1
2
Order By: Relevance
“…We found that in addition to this area, part of the cerebellar vermis was specifically activated, and we speculated that it was involved in sexuality during the excitement phase. Recently, the association of sexuality with the cerebellar vermis has been reported in other studies, including animal experiments 10) , which supports our results. We also found that during the plateau phase, the occipital lobe, which contains the visual cortex, and the temporal lobe, which contains the auditory cortex, became more highly activated than during the excitement phase, and in addition, the ventral striatum (putamen) was specifically activated (Figure-4) …”
Section: Analysis Of the Libido During Specific Sexual Activitysupporting
confidence: 93%
“…We found that in addition to this area, part of the cerebellar vermis was specifically activated, and we speculated that it was involved in sexuality during the excitement phase. Recently, the association of sexuality with the cerebellar vermis has been reported in other studies, including animal experiments 10) , which supports our results. We also found that during the plateau phase, the occipital lobe, which contains the visual cortex, and the temporal lobe, which contains the auditory cortex, became more highly activated than during the excitement phase, and in addition, the ventral striatum (putamen) was specifically activated (Figure-4) …”
Section: Analysis Of the Libido During Specific Sexual Activitysupporting
confidence: 93%
“…In men, sexual stimulation with visual or olfactory cues produces activity in the cerebellar cortex [1,2], and similar responses in non-human primates are also found after stimulation with odors from receptive females [3]. In our laboratory, we found that sensory sexual stimulation of male rats produces the highest significant activation of granule cells at lobules 6 to 9 of the vermis region [4]. Nevertheless, the execution of sexual behavior decreases the number of sensory activated neurons.…”
Section: Introductionsupporting
confidence: 69%
“…Sexual experience also activates the cerebellum. Sexually naïve male rats allowed to copulate to one ejaculation at 4-day intervals showed activation of the cerebellar vermis (notably lobule 7) whereas males given non-copulatory exposure to females had relatively little activation (Manzo et al, 2008). Using an identical paradigm, dynamic increases were found in GAD-65 (assessed by RT-PCR), the enzyme that converts glutamate into the inhibitory neurotransmitter GABA, during the first three ejaculations experienced by males that were sexually naïve at the beginning of the experiment (Bolivar-Duarte, Silva, Manzo, & Pfaus, 2012); however, this increase had dropped back to baseline levels by the fourth ejaculation.…”
Section: Neural Correlatesmentioning
confidence: 99%